African American Women in the Struggle of the Civil Rights Movement (1950-1960) - BELAHOUEL, Kheira (My University, 2020)
Many black women have played a great role in the Civil Rights Movement in America, from working as house servants to leading local civil rights organizations. This research sheds light on the sacrifices of the African American women, and their participation in the Civil Rights Movement and their success against white people who were the reason behind race discrimination. Historically, African Americans suffered horribly from poor conditions, racism, and injustice. These kinds of dilemmas contributed for the rise of Civil Rights Movement during the late 1950s and early 1960s. This movement liberated blacks and ensured total rights, equality between the two races. Within it, African American men and women worked hard to make people understand that America could be a state of harmony where no white superiority or black inferiority would exist. Indeed, black male leaders were mentioned as the ones who battled against Jim Crow Lows, while most of the African Americans Women remained anonymous, unsung heroes’. Even though, they participated on all levels of the Black Freedom Movement. These Women were fighting to achieve liberty from slavery, racism, and especially sexism.
Keywords: Civil Rights Movement; African American women; Slavery; Discrimination; Injustice; Liberty